Calidad molinera de la línea promisoria de arroz L-37 (Oryza sp.) en comparación con la variedad comercial SFL-11 en la zona Vinces, provincia de Los Ríos. - Zambrano Caisaguano, José Antonio (2025)
Rice (Oryza sativa L.) is the second most popular cereal in the world, considered one of the most important crops. The main objective of the research was to determine the milling quality of the promising rice line L-37 (Oryza sp.) compared to the commercial variety SFL-11 in the Vinces area, province of Los Ríos. The research was carried out at the “Mechita” farm, located on the Palizada Posa Seca road in the Vinces parish. For the analysis, three replications and two cultivars (L-37 and SFL-11) were considered. The experimental design was completely randomized, with the Tukey test. The results indicate that the L-37 rice milling line is a crucial research project in the genetic improvement of Ecuador, with the objective of releasing relevant agronomic varieties with good yields and acceptability for consumers. It was concluded that the milling quality of rice from the promising line L-37 compared to the variety SFL-11 is one of the relevant investigations within the genetic improvement that is being developed in Ecuador, at the Technical University of Babahoyo; the variables integral grain, white mass, whole grains and whiteness obtained superior results with the promising line L-37, compared to the control; it was evident that the content of amylose, protein and white center stood out in the variety SFL-11; however, this variety registered a greater amount of husk, dust and rice and the promising line L-37 adapted favorably in the area of Vinces, province of Los Ríos, Ecuador.